Activation and Deactivation of Gold/Ceria–Zirconia in the Low‐Temperature Water–Gas Shift Reaction. (15th November 2017) - Carter, James H.; Liu, Xi; He, Qian; Althahban, Sultan; Nowicka, Ewa; Freakley, Simon J.; Niu, Liwei; Morgan, David J.; Li, Yongwang; Niemantsverdriet, J. W. (Hans); Golunski, Stanislaw; Kiely, Christopher J.; et al.
Abstract: Gold (Au) on ceria–zirconia is one of the most active catalysts for the low‐temperature water–gas shift reaction (LTS), a key stage of upgrading H2 reformate streams for fuel cells. However, this catalyst rapidly deactivates on‐stream and the deactivation mechanism remains unclear. Using stop–start scanning transmission electron microscopy to follow the exact same area of the sample at different stages of the LTS reaction, as well as complementary X‐ray photoelectron spectroscopy, we observed the activation and deactivation of the catalyst at various stages. During the heating of the catalyst to reaction temperature, we observed the formation of small Au nanoparticles (NPs; 1–2 nm) from subnanometer Au species. These NPs were then seen to agglomerate further over 48 h on‐stream, and most rapidly in the first 5 h when the highest rate of deactivation was observed. These findings suggest that the primary deactivation process consists of the loss of active sites through the agglomeration and possible dewetting of Au NPs.